Cold and compression in the management of musculoskeletal injuries and orthopedic operative procedures: a narrative review - Jon E Block (Dove Medical Press, 2010)
Jon E BlockJon E Block, PhD., Incorporated, San Francisco, CA, USAAbstract: Cold and compression are routinely applied immediately after acute injury or following surgery to alleviate pain, reduce swelling and speed functional recovery. The objective of this literature review is to describe the published clinical findings regarding combined cold and compression therapy in the management of musculoskeletal injuries and after orthopedic operative procedures. Of 33 potential articles triaged, the findings of 21 randomized controlled trials were assessed and summarized. The findings reported by these 21 studies were largely subjective pain outcomes and, to a lesser degree, swelling and range of motion, and were inconsistent and divergent, making it difficult to recommend the most appropriate, effective clinical application of cold and compression. Further, 18 of the 21 reported studies evaluated cold and static compression, where the extent and duration of the compression was not uniform within or across studies. Operative procedures may offer a more controlled environment for rigorous investigations. However, such studies must be powered sufficiently to account for variations in surgical procedure that could affect outcomes. More uniform operative procedures, such as total knee arthroplasty, represent a well circumscribed intervention for studying the clinical utility of cold compression therapy because the operative technique is standardized, surgical tissue damage is extensive, intraoperative blood loss is high, and post-operative edema and pain are severe. Findings from randomized controlled trials of knee arthroplasty generally showed cold compression therapy provides better outcomes such as pain relief than alternative interventions. While the effects of cold and static compression are clearly better than no treatment, they do not appear to be directly additive.Keywords: cryotherapy, injury